The role of nonverbal communication in enhancing effective leadership in organizational contexts - Azhar, Fauzan (Gema Wiralodra, 2024)
In an era of business that continues to develop, successful effective leadership is the key for organizations to achieve their goals and maintain their competitiveness. The primary objective of this study is to examine how nonverbal communication contributes to leadership effectiveness. This research uses a qualitative literature study approach to explore the important role of nonverbal communication in improving effective leadership in an organizational context. Through literature analysis related to the concepts of nonverbal communication, leadership styles, and organizational dynamics, this research identifies key elements of nonverbal communication that can influence leadership effectiveness. The research results highlight the complexity of nonverbal communication interactions, including facial expressions, body language, and voice intonation, in the context of organizational leadership. The literature analysis also includes the positive impact of nonverbal communication on building interpersonal relationships, facilitating team communication, and strengthening the leadership image. This study also explores the challenges that may arise in understanding and managing nonverbal communication in diverse organizational contexts. This research provides in-depth insight into how understanding and mastering nonverbal communication can increase leadership effectiveness in managing organizational dynamics. The implications of this research are expected to provide practical guidance for leaders and professionals in developing their nonverbal communication skills to achieve more effective leadership in complex organizational environments.